Pharmacokinetics in Mouse and Comparative Effects of Frondosides in Pancreatic Cancer - Jasem Al Shemaili; Khatija Parekh; Robert Newman; Björn Hellman; Carl Woodward; Abdu Adem; Peter Collin; Thomas Adrian (Marine Drugs, 2016)
The frondosides are triterpenoid glycosides from the Atlantic sea cucumber Cucumaria frondosa. Frondoside A inhibits growth, invasion, metastases and angiogenesis and induces apoptosis in diverse cancer types, including pancreatic cancer. We compared the growth inhibitory effects of three frondosides and their aglycone and related this to the pharmocokinetics and route of administration. Frondoside A potently inhibited growth of pancreatic cancer cells with an EC50 of ~1 µM. Frondoside B was less potent (EC50 ~2.5 µM). Frondoside C and the aglycone had no effect. At 100 µg/kg, frondoside A administered to CD2F1 mice as an i.v. bolus, the Cpmax was 129 nM, Cltb was 6.35 mL/min/m2, and half-life was 510 min. With i.p. administration the Cpmax was 18.3 nM, Cltb was 127 mL/min/m2 and half-life was 840 min. Oral dosing was ineffective. Frondoside A (100 µg/kg/day i.p.) markedly inhibited growth cancer xenografts in nude mice. The same dose delivered by oral gavage had no effect. No evidence of acute toxicity was seen with frondoside A. Frondoside A is more potent inhibitor of cancer growth than other frondosides. The glycoside component is essential for bioactivity. Frondoside A is only effective when administered systemically. Based on the current and previous studies, frondoside A appears safe and may be valuable in the treatment of cancer.